Alveolar ridge preservation in the posterior maxilla reduces vertical dimensional change: A randomized controlled clinical trial - Cha, Jae‐Kook; Song, Young Woo; Park, Su‐Hyun; Jung, Ronald E.; Jung, Ui‐Won; Thoma, Daniel S. (Clinical oral implants research, 2019)
Objectives To test whether or not alveolar ridge preservation reduces vertical changes in the posterior maxilla compared to spontaneous healing following tooth extraction. Materials and methods Forty subjects requiring extraction of maxillary posterior teeth with root apices protruding into the maxillary sinus floor were consecutively enrolled. Patients were randomly assigned to either one of two surgical interventions: an alveolar ridge preservation procedure using collagenated bovine bone mineral and a resorbable collagen membrane (test) or no grafting (control). Cone‐beam computed tomographies were taken immediately and at 6 months after surgery, prior to dental implant placement. Results Based on radiographic data, the level of the sinus floor remained stable over time (baseline to 6 months) in the test group (−0.14 mm [−0.31, −0.02]). In the control group, the sinus floor level shifted more coronally (−1.16 mm [−1.73, −0.61]) than the test group (p < 0.05). The test group demonstrated a significantly larger residual bone height than the control group at 6 months (7.30 mm [6.36, 8.20] vs. 4.83 mm [3.94, 5.76], respectively, p < 0.05). Implant placement without any additional sinus augmentation procedure was performed in 42.9% of test group cases, whereas in all of the subjects in the control group an additional augmentation procedure was needed (100% of the cases). Conclusion Alveolar ridge preservation in the posterior maxilla maintained the vertical bone height more efficiently and resulted in less need for sinus augmentation procedures at 6 months compared to spontaneous healing.